MEMBENTUK WELL-BEING WIRAUSAHA PEREMPUAN DI INDONESIA : PERAN FLEXIBLE WORKING ARRANGEMENT DAN WORK-LIFE BALANCE - Ratih Indriyani (Universitas Sarjanawiyata Tamansiswa, 2025)
Nowadays, well-being is an important aspect that many female entrepreneurs strive for. This study aims to examine the effect of flexible working arrangements and work-life balance on well-being. This study also wants to examine flexible working arrangements on well-being with work-life balance as a mediating variable. The respondents of this study were female entrepreneurs in Indonesia. The research method used is explanatory quantitative research. This study uses a purposive sampling technique. This study selects female entrepreneurs in Indonesia who have run a business for at least 1 year. This study uses 150 female entrepreneurs in Indonesia as research respondents. The population of this study is female entrepreneurs in Indonesia and have run a business for at least 1 year. The data processing technique uses Smart PLS software. The results of the study indicate that flexible working arrangements have a significant effect on well-being. This study provides results that flexible working arrangements have an effect on work-life balance among female entrepreneurs in Indonesia. Interestingly, this study also found that work-life balance mediates the effect of flexible working arrangements on well-being. In other words, work flexibility increases well-being indirectly through the role of work-life balance as a mediator.